Enigmatic role of vagal network as a construction worker on thyroid gland creation by inspiration from neurohistology studies (Annals of Medical Research, 2021)
Aim: Thyroid functions regulate higher brain centers and olfactory informations are wireless universal stimulators for thyroid hardware and software development by way of vagal complex management. We wonder if thyroid architecture and functions are regulated by vagal nerve.Material and Methods: The animals were divided to three groups according to their T4 hormone levels which 1.89±0.10 µg/dl values was accepted as normal (G0; n=12); 2.13±0.19 µg/dl values was accepted as hyperfunctioned (GI; n=7) and 1.61±0.09 µg/dl values was accepted as hypofunctioned (GII; n=5). All of the thyroid glands, thyroidal branches of vagal nerves and brainstem section at the level of motor nucleus of vagal nerves sections were stained with haematoxylin-eosin, GFAP and tunnel dye for histological examination. All microscopical Stereological evaluations were done to understand how vagal morphology effects thyroid tissue architectures and T4 levels. All of the thyroid glands, thyroidal branches of vagal nerves and vagal motor nucleus evaluated stereologically to recognise whether some histomorphological variations thyroid follicles and volumes per cubic centimeter compared with thyroid hormone levels statistically.Results: The mean neuron density of vagal nucleus (NDVN), axon density of thyroidal branches of vagal nerves (TBVN), TFV, and T4 levels were measured as G0;GI and GII consequtively: (312±91)x106/mm3, 19.543±2.321/mm2, 1.89±0.10 µg/dl and (296±72)x106µm3/cm3 in G0; (387±93)x106/mm3, 22.576±2.864/mm2, 2.13±0.19 µg/dl and (331±65)x106µm3/cm3 in GI and (245±56)x106/mm3, 12.432±1.234mm2, 2.13±0.19 µg/dl and (231±45)x106µm3/cm3 in GII. Conclusion: It seems that decrased hormone levels due to ineffective/unadequate thyroid gland development results from inadequately developing vagal complex architecture.
Keywords: Vagal network; thyroid innervation; thyroid